THE BELT AND ROAD INITIATIVE (BRI): IMPLICATIONS FOR IRAN-CHINA RELATIONS - Osiewicz, Przemysław (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2018)
The article focuses on the Belt and Road Initiative, which was introduced by the leadership of the People’s Republic of China in 2013, and its political as well as economic implications for Iran-China relations. The ongoing implementation of the Chinese initiative raises a few research questions. Would both sides benefit from the cooperation in the BRI framework or would one of them maybe have the upper hand? What are the main opportunities and challenges in the case of China-Iran relations and BRI implementation? The analysis is conducted in the framework of the grand strategy theory. This study is based on primary sources such as official governmental documents, speeches of influential politicians, and official statistical data. Besides these sources, information from secondary sources like monographs and academic articles was taken into consideration.

Niniejszy artykuł jest poświęcony chińskiej inicjatywie pasa i drogi (BRI - the Belt and Road Initiative) oraz możliwych konsekwencji jej realizacji dla stosunków dwustronnych pomiędzy Chinami i Iranem. Okoliczności procesu implementacji głównych założeń inicjatywy budzą wątpliwości już na jego wstępnym etapie. W tym kontekście należy postawić dwa istotne pytania badawcze. Czy obie strony odniosą porównywalne korzyści w ramach realizacji BRI, czy też jedna z nich zyska wyraźną przewagę? Jakie są główne szanse oraz zagrożenia dla stosunków irańsko-chińskich, wynikające z implementacji założeń BRI? Analiza została przeprowadzona w ramach teorii wielkiej strategii, zwłaszcza odnośnie do możliwości jej wykorzystania w przypadku BRI. Badaniu poddane zostały zarówno aspekty polityczne, jak i ekonomiczne. Podstawę źródłową stanowią oficjalne dokumenty, wypowiedzi czołowych polityków oraz dane statystyczne. Ponadto, w trakcie pracy wykorzystane zostały wybrane monografie oraz artykuły naukowe.
CHIŃSKIEJ REPUBLIKI LUDOWEJ Z IRANEM
Keywords: the Belt and Road Initiative; BRI; China; Iran; the New Silk Road; grand strategy; inicjatywa pasa i drogi; Chiny; Iran; Nowy Jedwabny Szlak; wielka strategia